Breakage of single-stranded DNA by rat liver nicking-closing enzyme with the formation of a DNA-enzyme complex. - Been, M D (1980)
The DNA nicking-closing enzyme (type I topoisomerase) from rat liver nuclei breaks single-stranded DNA. The broken strand contains a 5'-hydroxyl and tightly bound protein. The stability of this protein-DNA complex to high salt, alkali and detergent suggests a covalent linkage between the DNA and the enzyme. The observed breakage of single-stranded DNA occurs at neutral pH prior to treatment with alkali or detergent, indicating that the breakage may be the result of an interrupted nicking and closing cycle. The resulting covalent complex could represent a reaction intermediate in the overall nicking-closing reaction.